2020
DOI: 10.3389/fphys.2020.00359
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Different Replacement Levels of Fishmeal by Fish Silage Could Influence Growth of Litopenaeus vannamei by Regulating mTOR at Transcriptional Level

Abstract: Fish silage (FS) has been confirmed as a high-quality feed ingredient because of its balanced nutrition, low cost, and environmental friendliness. In the present study, we evaluated the performance of replacing fishmeal by FS in the diet of white shrimp, Litopenaeus vannamei. Five isonitrogenous (410 g kg −1) and isolipidic (75 g kg −1) diets were formulated with replacement of fishmeal by 0% (FM), 25% (FS25%), 50% (FS50%), 75% (FS75%), and 100% (FS100%) FS. After an 8-week trial, shrimps fed low FS diets (FM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Hepatopancreas in the crustacea play an essential role in nutrient absorption and metabolism, so it is important to understand whether the substitution level of fishmeal and changes of the dietary amino acids are linked with changes in the transcription of genes known to participate in protein absorption and metabolism. To date, limited data were reported about the relationship between the dietary amino acid supplementation and the TOR signalling pathway in shrimp and how fishmeal level affects TOR signalling pathway (Shao et al, 2020;Xie, Wei, Chen, et al, 2020). Also, TOR is appreciated to be a vital link between immune function and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatopancreas in the crustacea play an essential role in nutrient absorption and metabolism, so it is important to understand whether the substitution level of fishmeal and changes of the dietary amino acids are linked with changes in the transcription of genes known to participate in protein absorption and metabolism. To date, limited data were reported about the relationship between the dietary amino acid supplementation and the TOR signalling pathway in shrimp and how fishmeal level affects TOR signalling pathway (Shao et al, 2020;Xie, Wei, Chen, et al, 2020). Also, TOR is appreciated to be a vital link between immune function and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of dietary BSF on the intestinal health remains unknown. Excessive replacement of FM may lead to impaired nutritional sensitivity and metabolism (Xu et al, 2016;Shao et al, 2020). Besides, intestinal histology is directly related to the digestion and absorption of nutrients by the shrimp, thus affecting growth.…”
Section: Discussionmentioning
confidence: 99%
“…Digestibility and growth studies have shown that fish silage is highly digestible and can be used to replace up to 75% of fishmeal in aqua-feeds [52]. For shrimp, Litopenaeus vannamei fed with 25% to 50% silage-based diets showed higher growth performance [51,114] and improved gut health [54]. Fish silage not only acts as a feed ingredient but also an essential feed additive [32].…”
Section: Discussionmentioning
confidence: 99%